Assessing the individual and cumulative impacts of drivers in food systems transformation through a multi-model ensemble paradigm - Sundiang, Marina; Oliveira, Thais Diniz; Mason-D'Croz, Daniel; Gibson, Matthew; Beier, Felicitas; Benavidez, Lauren; Chepeliev, Maksym; Doelman, Jonathan; Dunston, Shahnila; Fujimori, Shinichiro; Hasegawa, Tomoko; Havlik, Petr; et al. (Purdue University, 2024)
The global food system faces a triple challenge: ensuring accessible healthy diets for all while promoting fair production, processing, and distribution, within safe planetary boundaries. Unfortunately, it significantly contributes to transgressing these boundaries. Intensified production driven by population growth depletes resources, exacerbates biodiversity loss, and worsens the climate crisis. Despite producing enough for 10 billion people, distribution remains uneven, leaving one in ten food insecure. Existing consumption patterns reinforce this imbalance. Failure to act risks exacerbating food inequality, malnutrition, and crossing irreversible tipping points. Leveraging global economic models, we find that a comprehensive approach combining productivity gains and diet shifts maximizes environmental benefits. Implementing these interventions together can meet agricultural demands without further land conversion or increased emissions. Combining this with climate change mitigation and land-use regulations maximizes environmental benefits and offsets food affordability challenges associated with ambitious mitigation efforts.